THE EFFECT OF FRAUD DIAMOND AND TECHNOLOGY ON FRAUD TENDENCIES OF AUTOMOTIVE DEALERSHIPS EMPLOYEES IN MALANG - Pambudi, Kharisma Oktavian (Jurnal Ilmiah Mahasiswa FEB, 2016)
This   research   aims   to   analyse   the   effect   of   pressure, opportunity, rationalization, capability and technologyon the fraud tendency of employees. The population of this study is employees of automotive dealerships located in Malang City.Using a convenience sampling method, 60 respondents are selected as samples. The data analysis technique used in this research is the multiple linear regression analysis.The results of this research indicate that the pressure, opportunity, rationalization, capabilityand technology positively affects the fraud tendency of Malang  automotive  dealerships  employees.  This  also  shows  that  the  fraud diamond and technology have an influence on the occurrence of fraud committed by employees of Malang automotive dealerships.Keywords:  Pressure, Opportunity, rationalization, Capability, Technology and Tendency Of Fraud Employees